How you get it matters: Moderating role of transfer method in guiding ownership assignments for modified objects - Li, Zhanxing; Dong, Dong (Frontiers in Psychology, 2023)
Introduction Previous research has found that value change and creation drive people to support the laborer more than the original owner in ownership reasoning for modified objects; however, the transfer methods used to resolve conflicts have largely been ignored. In this work, two studies were designed to investigate the role of value change and creation in adults’ labor-based ownership judgments in four transfer conditions (i.e., take/steal/borrow/find). Methods Scenarios involving different extent of value change and creation in different transfer ways were presented to Chinese adult subjects after which they were asked to judge who is the owner. Results People were more likely to assign ownership to the original owner in the take, steal and borrow conditions but not in the find condition, and this reasoning held regardless of whether the original materials showed high or low value appreciation or successful creation, and it was applicable to raw materials with low (Study 1) and high values (Study 2). In addition, the effect of value change and creation on ownership reasoning varied according to different transfer methods. Conclusion The results suggest the moderating role of transfer method in people’s ownership assignments, which will provide insights for real-life mediation of ownership conflicts.